2023
DOI: 10.1182/bloodadvances.2021006563
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR expression on monocytes and outcome of anti-CD19 CAR T-cell therapy for large B-cell lymphoma

Abstract: Despite their unprecedented success in relapsed/refractory (R/R) large B-cell lymphoma (LBCL), anti-CD19 CAR-T cells are associated with significant toxicities, and more than half of the patients will relapse. As monocytes emerged as key players in CAR therapy, we sought to evaluate the evolution of HLA-DR expression on monocytes (mHLA-DR) prior to and following commercial anti-CD19 CAR-T cell infusion in a large cohort of 103 patients with R/R LBCL, and its association with adverse events and treatment respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Bourbon E et al found that the change of HLA-DR expression on monocytes (mHLA-DR) before and after infusion of anti-CD79 CAR T cells in patients with relapsed/refractory (R/R) large B-cell lymphoma (LBCL) was related to adverse events and therapeutic effect. The level of mHLA-DR decreased after lymphocyte depletion, which was related to poor results (Bourbon et al 2023). Monocyte disorder before lymphocyte depletion is characterized by downregulation of mHLA-DR, which is related to in ammation and immunosuppression of tumor environment, and to the failure of anti-CD19 CAR T cells in patients with recurrent/refractory large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Bourbon E et al found that the change of HLA-DR expression on monocytes (mHLA-DR) before and after infusion of anti-CD79 CAR T cells in patients with relapsed/refractory (R/R) large B-cell lymphoma (LBCL) was related to adverse events and therapeutic effect. The level of mHLA-DR decreased after lymphocyte depletion, which was related to poor results (Bourbon et al 2023). Monocyte disorder before lymphocyte depletion is characterized by downregulation of mHLA-DR, which is related to in ammation and immunosuppression of tumor environment, and to the failure of anti-CD19 CAR T cells in patients with recurrent/refractory large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In BCL, CAR T-cell failure was correlated with tumor volume, extranodal sites ≥2, and a decreased expression of HLA-DR on monocytes. 5 , 15 …”
Section: Patient Diseasementioning
confidence: 99%